The Role of the Arabic Language in Shaping and Preserving Islamic Culture in the Modern Era - Lalu Ali Hasan; Layla Hassan (IJAS: International Journal of Arabic Studies, 2026)
Arabic Islamic culture is a fundamental aspect of Islamic civilization that integrates language, religion, and social practices into a unified and meaningful cultural system. This study aims to examine the role of the Arabic language in shaping, preserving, and transmitting Islamic cultural identity, as well as to analyze its relevance in contemporary society. The research employs a qualitative approach using library research methods, drawing from classical Islamic texts, academic literature, and recent scholarly discussions. The findings indicate that Arabic functions not only as a communication tool but also as a sacred medium for conveying Islamic teachings, particularly through the Qur’an and religious rituals. In addition, cultural expressions such as Arabic literature and calligraphy reflect the deep connection between spirituality and artistic creativity within Islamic traditions. The study also reveals that Arabic Islamic culture is embedded in everyday life, influencing values, behavior, and social interactions among Muslim communities. Despite challenges posed by globalization, Arabic Islamic culture remains adaptable through education and digital media. Therefore, it continues to play a vital role in maintaining Islamic identity and ensuring cultural continuity in the modern era.